Postpartum depression: Prevention and multimodal therapy - Anca Daniela Stanescu; Denisa Oana Balalau; Liana Ples; Stana Paunica; Cristian Balalau (Journal of Mind and Medical Sciences)
A woman goes through many biological (hormonal, physical), psychological (emotional), and socio-cultural changes during pregnancy. Furthermore, changes also occur in the mother's familial and interpersonal world after childbirth. While some mothers have positive emotions at birth, such as joy and pleasure, others complain of negative experiences varying from sadness and depression to psychosis. Thus, the risk of depression is higher for women during the postpartum period, having a tendency to decrease in most cases over the first 2 weeks after delivery. Unfortunately, this favorable evolution does not happen in about 1 in 4-7 women, who develops postpartum depression. Postpartum depression has generally the same features as any common depressive episode encountered at any other time in life. However, assessment of depressive symptoms in the parental period implies not only general tools (such as the Depression Scale of the Center for Epidemiological Studies or the Beck Depression Inventory), but also a specific evaluation using the Edinburgh Postnatal Depression Scale. Taking into account all changes that occur during the peripartum period, a multimodal approach for postpartum depression would be recommended, including an appropriate lifestyle (walks, ambient environments), counseling, cognitive-behavioral therapy, and finally antidepressant medication when required. As a conclusion, postpartum depression may range from a mild and reversible episode to a severe and persistent form. Antepartum and postpartum screening, an early diagnosis, and a tailored approach to depression are essential for better results and prognosis related to both mother and child.